Persepsi Etnis Tionghoa tentang Pendidikan di Komplek Waringin Indah Kota Medan - Yovana Julietta; Wira Firmansyah (Laboratory of Anthropology Department of Cultural Science Faculty of Halu Oleo University, 2024)
This research aims to determine the perceptions of ethnic Chinese about education, determine the cultural values of ethnic Chinese that influence education, and determine the preferences of ethnic Chinese parents in choosing formal education and non-formal education. The research method used is qualitative research with a descriptive approach. Data collection techniques were obtained from observation, interviews, and documentation using data analysis techniques in data reduction, data presentation, and conclusions drawing. The theory used in this research uses Lev Vygotsky's sociocultural theory. This theory teaches that the social environment, including parents and friends, influences children's learning development. The research results show that ethnic Chinese place great importance on education, one of which is ethnic Chinese parents who send their children to high school because they have the view that education is essential in order to have a bright future. Education is also inseparable from the cultural values of ethnic Chinese, such as honesty, discipline, politeness, enthusiasm and the cultural value of hard work. These cultural values greatly influence perceptions about education and success in achieving the future. Parents have good preferences when choosing formal education, one of which is the quality of the school and the distance between the school and where they live. Not only formal education but ethnic Chinese parents also prefer non-formal education, namely the quality of good study guidance and the talents or abilities of their children.